Analysis of verbs in the writing of EFL Mongolian writers / Uyanga Narangerel - Uyanga, Narangerel (2012)
The present study investigates error found in 45 Mongolian students’ English language essays. Participants were final year students majoring in English from the University of Humanities, in Ulaanbaatar, Mongolia. All participants identified their English proficiency level as “advanced” and they are to receive a Bachelors Degree of “English Language Teacher” upon graduation. Data were collected through simple random sampling of students from EFL courses who were then asked to participate in an essay writing task by choosing one of three available topics. In order to make the project more comprehensive, all errors were identified by three independent instructors: one English grammar instructor from the University of Humanities, one native English speaking instructor from the Mongolian National University and the researcher herself who is a teacher of Russian and English, who is studying for her Master’s Degree in English as a Second Language at the University of Malaya in Kuala Lumpur, Malaysia. All three worked separately. The findings from the students’ practical study of errors in written essays were integrated with research on possible causes of errors. Findings from this research show that participants have major difficulties in the following areas: verb tenses, choice of appropriate words, prepositions, and spelling .Major causes of verb errors are mainly attributed tense errors, subject-verb agreement, auxiliary verbs and verb form errors.